PERSEPSI MASYARAKAT TENTANG OBJEK WISATA LORONG BASAH NIGHT CULINARY KOTA PALEMBANG - Desi Ismiralia; Lisnini Lisnini; A Jalaludin Sayuti (Politeknik Negeri Bengkalis, 2019)
The purpose of this research is to get know about: how the society's perception of Lorong Basah Night Culinary which is reviewed from for tourismcomponents are attractions, amenitas, accessibility and hospitality based on the perception of the people who have visited. The benefits of this research as a contribution to develop tourism components in Lorong Basah Night Culinary in order to continue to be known as a culinary tourism destination in the city of Palembang. This research is quantitative research with respondents cosisting of 115 society’s who have visited in Lorong Basah Night Culinary. The determinination of respondents by accidental sampling data collection is done by questionnaires, interview, documentation, and literature study. The result of the questionnaires is measured by using Likert scale then interpreted. The results represent that most society’s perceptions showed agree of the categories from four tourism components in Lorong Basah NightCulinary, but the scoring results show a small percentage of the accessibility component isabout 65% because there is one indicator in the neutral categoryand small result too of amenities component is amount to 65.6% because there are two indicators in the neutral category.